Edukasi Kesehatan dan Keselamatan Kerja bagi Pelaku UMKM Sari Raos Desa Pedawang Kabupaten Pekalongan - Aria Mulyapradana; Aghus Jamaludin Kharis; Farikhul Muafiq; Safna Saqinah; Nafiatul Manahilkhakim (Solusi Bersama : Jurnal Pengabdian dan Kesejahteraan Masyarakat, 2024)
The knowledge possessed by the MSME actors of Sari Raos Pedawang Village regarding Occupational Health and Safety is still minimal. The lack of knowledge will have a bad impact on business actors because the potential for occupational hazards is always present at the production site in order to minimize occupational hazards, so the team initiated to hold education on the K3 program. The purpose of this activity is to increase the knowledge of business actors about Occupational Health and Safety and anticipate the occurrence of occupational hazards at production sites. The methods used are lectures, questions and answers, and discussions. The participants of this activity were 25 people from Sari Raos MSMEs in Pedawang Village. The Village Head and MSME Actors of Sari Raos welcomed the positives of this activity, the results of this activity concluded that the material presented by the team was very appropriate and needed by the Sari Raos MSME Actors to prevent work hazards during work activities and occupational health for business actors. The hope after participating in this activity is that participants can increase their knowledge and implement it at the work site.